Isolation and identification of Alicyclohacillus genus bacteria in domestically produced apple juice concentrates - M. N. Kurbanova; M. V. Trishkaneva; Zh. A. Semenova; A. Yu. Kolokolova; M. T. Levshenko (Аграрная наука Евро-Северо-Востока, 2018)
The article provides the results of studies on the identification of Alicyclobacillus genus bacteria in apple juice concentrates produced at the processing enterprises of the Southern Federal District of the Russian Federation. Microorganisms of the genus Alicyclobacillus are acid resistant, thermophilic, spore-forming bacteria that can cause juice products spoilage. Spoilage mainly appears as the formation of a phenolic (medicinal or smoky) smell. An alien odor is the result of the formation of guaiacol (2-methoxyphenol), the product of the vital activity of separate strains (guaiacol-forming) bacteria of Alicyclobacillus genus. Microbiological studies of 49 samples of sterilized apple juice concentrates and 10 samples of washing water from the equipment, selected in the process of apple juice concentrate producing were carried out. The studies have shown that spores of Alicyclobacillus genus bacteria can remain viable in juice concentrates after the heat treatment commonly used in the food processing industry for microbiological stability. Microbiological analysis of 49 samples of apple juice concentrates showed that 30 samples (61% of the total number of examined samples) contained bacteria of the genus Alicyclobacillus. When identifying bacteria of Alycyclobacillus genus in 30 samples of apple juice concentrates containing these bacteria, 25 samples (83%) contained guaiacol-positive bacteria and, accordingly, 5 samples (17%) contained guaiacol-negative bacteria. The number of bacteria in 1 cm3 of apple juice concentrates did not exceed 400 CFU/cm3. The results of the research can serve as the basis for the development of standards concerning the allowable content of Alicyclobacillus bacteria in apple juice concentrate.